Eurex-LUNa Abisko Trials Stereo Camera Calibration - Wehbe, Bilal; Creutz, Tom; Hildebrandt, Marc; Wirtz, Marius; Zipper, Michael (Zenodo, 2022)
Bottom Stereo Camera Calibration Images for AUV Deepleng. They should be used for both determining intrinsic as well as extrinsic calibration parameters for the bottom-looking stereo camera. This is necessary for the image data published with DOI 10.5281/zenodo.7035119 . Contact: tom.creutz@dfki.de, bilal.wehbe@dfki.de Funded by BMWi (Kennziffer 50 NA 2002)